DIFFERENCES IN PERFUSION AND REGIONAL FUNCTIONAL ABNORMALITIES IDENTIFIED BY REST GMPS IN DILATED CARDIOMYOPATHY PATIENTS WITH ISCHEMIC AND NON ISCHEMIC ETIOLOGY BASED ON CORONARY ANGIOGRAPHY RESULTS - Muhammad Shahzad Afzal; Hamid Saeed; M. Saeed Akhtar et al. (Journal of University Medical & Dental College, 2016)
ABSTRACT: Dilated Cardiomyopathy (DCM) is a common problem and it is very important to differentiate its ischemic cause from nonischemic for management and prognostic purposes. OBJECTIVE: To evaluate rest gated myocardial perfusion scintigraphy (GMPS) in patients with ischemic and nonischemic DCM, categorized on the basis of coronary angiography, and to compare mean summed perfusion score (SPS), mean summed thickening score (STS) and mean extent of perfusion abnormality (EPA) between them. DESIGN: Descriptive case series. PATIENTS & METHODS: This study was conducted at Nuclear Cardiology department of Punjab Institute of Nuclear Medicine (PINUM), Faisalabad over a period of six months from 0101-2013 to 30-06-2013. Resting GMPS were performed in 102 known patients of DCM (aged 17 to 70 years with a mean age of 49.12 ± 11.8 years, 86 Male and 16 Female) by injecting 20 mCi of 99mTc-MIBI. Patients were subdivided into ischemic (n=74) and nonischemic subgroup (n=28) by using the coronary angiography results. Summed perfusion score (SPS), summed thickening score (STS) and extent of perfusion abnormality (EPA) were calculated by using twenty segment model. Results of GMPS were compared between ischemic DCM and nonischemic DCM by using independent samples t-test. P-value of <0.05 was taken as statistically significant. RESULTS: SPS and EPA are significantly higher in ischemic than non ischemic sub groups (26.46 ± 10.80 Vs 7.86 ± 5.13 P<0.001, and 7.16 ± 1.97 vs 4.32 ± 1.70 P<0.001 respectively). STS was significantly higher in non ischemic group than ischemic group of DCM patients (33.21 ± 7.13 vs 23.99 ± 7.81). CONCLUSION: Our study shows that there are statistically significant differences in the values of summed perfusion score, summed thickening score and extent of perfusion abnormalities between ischemic and non ischemic DCM groups, calculated by using rest gated myocardial perfusion scintigraphy. Combined evaluation of the perfusion and wall thickening on rest gated myocardial perfusion scintigraphy is useful to identify ischemic and nonischemic etiology of DCM.